Does democracy protect the environment? The role of the Arctic Council - Mavisakalyan, Astghik; Otrachshenko, Vladimir; Popova, Olga; Justus Liebig University Giessen (My University, 2023)
This paper examines the influence of democratic institutions on environmental policy stringency and the degree to which it is affected by membership in the Arctic Council. We hypothesize that, relative to countries with no Arctic presence, countries present in the Arctic given their territorial, trade, and touristic interests are more pro-environmentally inclined as they experience the effects of global warming first-hand, and the quality of democratic institutions may reinforce this effect. Our empirical analysis based on global macroeconomic data suggests that countries with democratic institutional environments are associated with more response to Arctic status and more stringent environmental policies. Moreover, the presence of democratic governments in the Arctic increases the stringency of both market- and non-market-based environmental regulations. The suggestive estimated monetary value associated with the impact of democratic institutions in the Arctic is about 101,000 international dollars per capita. These findings underscore that the development of democratic institutions may lead to strong welfare improvements and can be used in the design of international environmental agreements for Arctic area protection.